Opera Journeys' Guide : Met Opera HD Simulcasts 2008-2009 Season. - Fisher, Burton D. (Opera Journeys Pub., 2008)
Opera Journeys' Guide to 10 operas in the hugely popular Met Opera HD Simulcasts 2008-2009 series features Cast and Credits, Principal Characters, Brief Story Synopsis, Story Narrative with Music Highlight Examples, and Burton D. Fisher's insightful and in depth Commentary and Analysis. The featured operas are: Salome (R. Strauss), Doctor Atomic (Adams), La Damnation de Faust (Berlioz), Thais (Massenet), La Rondine (Puccini), Orfeo ed Euridice (Gluck), Lucia di Lammermoor (Donizetti), Madama Butterfly (Pussini), La Sonnambula (Bellini), La Cenerentola (Rossini).